JENIS-JENIS ARACEAE DI HUTAN WISATA DAN CAGAR ALAM PLAWANGAN - TURGO YOGYAKARTA - Hendro Kusumo EPM (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Abstract-Mount Merapi since 1006 until now still erupting actively. Every three years erupting hot clouds and lava heat (Drajat et al., 1994; Sukandarrumidi & Sudibyakto , 1994). Location of Mount Merapi in Yogyakarta with a climate transition from wet to dry (West Java - East Java). Mountain with physical environment, chemical, and biotic, different than other volcanoes in Indonesia (Backer & Bakhuizen van den Brink, 1968; Whitten et al., 1996). Inventarization the species of plants is very important to do, especially as the floristic composition of the vegetation resources Araceae. The purpose of this study to identify the types of plants of Araceae on certain limits in Nature Reserve Plawangan-Turgo, South slope of Mount Merapi. The study was conducted by the survey method in the southern slopes of Mount Merapi at an altitude of 900-1.275 m.dpl. Collection of plants of Araceae made a herbarium. Sample identified in Plant Taxonomy laboratories, Biology UGM. Identification is based on morphological characteristics using identification books, revision, flora, and atlases to species level. There are 10 types Araceae, which are grouped in 7 Genus, namely : Aglaonema simplex BI., Alocasia heterophylla Merr., Arisaema filiforme BI., Colocasia antiquorum Schott , Colocasia gigantea (BI) Hook.f., Rhaphidophora montana (BI) Schott, Schismatoglottis rupestris Zoll., Scindapsus hederaceus (Z&M)Miq., Scindapsus perakensis Hook.f., Scindapsus sp. Commonly, Araceae have habitus vines with or without the rhizome. This is because habitat conditions are shaded canopy of large trees that routine 3-5 years exposed as a result of the burning hot clouds of Mount Merapi. Keywords : Araceae , nature reserve Plawangan – Turgo.